Effects of snack intake during pregnancy and lactation on reproductive outcome in mild hyperglycemic rats - Martins, Marina Galleazzo [UNESP]; Cruz, Alessandra Gonçalves da [UNESP]; Oliveira, Giovana Pereira de [UNESP]; Woodside, Barbara; Horta-Júnior, José de Anchieta de Castro e [UNESP]; Kiss, Ana Carolina Inhasz [UNESP] (Elsevier, 2021)
Metabolic disorders, like diabetes, as well as maternal diet, alter nutrient availability in utero, inducing adaptations in the offspring. Whether the effects of maternal hyperglycemia are modulated by diet, however, has yet to be explored. In the current study, we examined this issue by giving females rats, treated neonatally with STZ to induce mild hyperglycemia, and control littermates either ad libitum access to standard chow (Control n = 17; STZ n = 16) or standard chow and snacks (Control-snack n = 18; STZ-snack n = 19) (potato chips and a red fruit-flavored sucrose syrup solution 1.5%) throughout pregnancy and lactation. We hypothesized that the maternal glucose intolerance typically seen in female rats treated neonatally with STZ would be exacerbated by snack intake, and that the combination of snack intake and STZ treatment would lead to alterations in maternal behavior and offspring development. Maternal body weight and food intake were measured daily through pregnancy and lactation and litter weight throughout lactation. At birth, litter size, offspring weight, body length, and anogenital distance were obtained and offspring were classified according to their weight. Measures of nursing and retrieval behavior, as well as exploration in the open field and the elevated plus-maze were also recorded. As predicted, snack intake tended to aggravate the glucose intolerance of STZ-treated rats during pregnancy. Both Control and STZ-treated females that had access to snacks ate more calories and fat, but less carbohydrate and protein than females having access to chow alone. Overall, STZ-treated dams gave birth to fewer pups. Chow-fed STZ females gave birth to a greater proportion of large for pregnancy age pups, whereas dams in the Control-snack group gave birth to a greater proportion of small pups. The birth weight classification of pups born to STZ-snack rats, however, resembled that of the Control chow-fed females. Although all litters gained weight during lactation, litters from snack-fed dams gained less weight regardless of maternal hyperglycemia and did not show catch-up growth by weaning. Overall, STZ rats spent more time nest building, whereas the average inter milk ejection interval was higher in snack-fed females. STZ-snack dams retrieved the complete litter faster than dams in the other groups. Together, these data suggest that when mild hyperglycemic females are given access to snacks throughout pregnancy and lactation their intake is similar to that of Control females given snack access. The combination of hyperglycemia and snack access tended to decrease glucose tolerance in pregnancy, and normalized birth weight classification, but produced few other effects that were not seen as a function of snack intake or hyperglycemia alone. Since birth weight is a strong predictor of health issues, future studies will further investigate offspring behavioral and metabolic outcomes later in life.
Keywords: Birth weight; Hyperglycemia; Lactation; Maternal behavior; Nutrition; Pregnancy